Ascorbic acid is essential for the release of insulin from scorbutic guinea pig pancreatic islets. - Wells, W W (1995)
Pancreatic islets from young normal and scorbutic male guinea pigs were examined for their ability to release insulin when stimulated with elevated D-glucose. Islets from normal guinea pigs released insulin in a D-glucose-dependent manner showing a rapid initial secretion phase and three secondary secretion waves during a 120-min period. Islets from scorbutic guinea pigs failed to release insulin during the immediate period, and only delayed and decreased responses were observed over the 40-60 min after D-glucose elevation. Insulin release from scorbutic islets was greatly elevated if 5 mM L-ascorbic acid 2-phosphate was supplemented in the perifusion medium during the last 60 min of perifusion. When 5 mM L-ascorbic acid 2-phosphate was added to the perifusion medium concurrently with elevation of medium D-glucose, islets from scorbutic guinea pigs released insulin as rapidly as control guinea pig islets and to a somewhat greater extent. L-Ascorbic acid 2-phosphate without elevated D-glucose had no effect on insulin release by islets from normal or scorbutic guinea pigs. The pancreas from scorbutic guinea pigs contained 2.4 times more insulin than that from control guinea pigs, suggesting that the decreased insulin release from the scorbutic islets was not due to decreased insulin synthesis but due to abnormal insulin secretion.